Ibnu Athaillah dan Penafsiran Esoteric: Urgensitas Pemikiran Ibnu ‘Athai’illah As-Sakandari dalam Nuansa Sufistik - Rozi, Fathur (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2021)
This paper discusses about Ibn 'Athoillah As-Sakandari’s thought in performing esoteric interpretations to religious texts. The Hadith said that the Qur'an has dimension of esoteric meaning, extrinsic and esoteric, internal historically had implications for inevitability of esoteric Qur'an’s interpretation, especially by and for Sufi. But the existence of this interpretation is diverse, both in terms of epistemological and methodological. So this considered important for author to discuss the discourse of Ibn Atha'illah's thoughts and his efforts to explain the content of Qur’an by means of esoteric interpretation. This research uses qualitative research methods with library research methods. It mean, inspect and researching the sources of literature and using written materials in form classical books, books and other written sources related with the theme discussion. The subject studied in this paper is what is behind ibn Athoillah's thoughts and how ibn 'Athoillah interprets religious texts with esoteric interpretations. This paper is a literature research and the historical approach, so the author concluded that 1) ibn Athoillah’s esoteric interpretation has historical legitimacy during the Prophet Muhammad saw and theology from Qur'an and Sunnah; 2) Esoteric interpretation should be based on the literal meaning, textual verse and Esoteric interpretation the source is the individual wijdaniyyah of Sufi.